2020
DOI: 10.3389/fcell.2020.00561
|View full text |Cite
|
Sign up to set email alerts
|

Adipogenesis, Osteogenesis, and Chondrogenesis of Human Mesenchymal Stem/Stromal Cells: A Comparative Transcriptome Approach

Abstract: Adipogenesis, osteogenesis and chondrogenesis of human mesenchymal stem/stromal cells (MSC) are complex and highly regulated processes. Over the years, several studies have focused on understanding the mechanisms involved in the MSC commitment to the osteogenic, adipogenic and/or chondrogenic phenotypes. High-throughput methodologies have been used to investigate the gene expression profile during differentiation. Association of data analysis of mRNAs, microRNAs, circular RNAs and long non-coding RNAs, obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(80 citation statements)
references
References 176 publications
(354 reference statements)
4
72
0
4
Order By: Relevance
“…Further, isolated MSCs were stained with rhodamine phalloidin (selectively binds to F-actin) and DAPI to study their morphological features. MSCs have the potential to differentiate into various lineages ( Robert et al., 2020 ). Subsequently, the MSC were checked for their adipogenic and osteogenic differentiation characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Further, isolated MSCs were stained with rhodamine phalloidin (selectively binds to F-actin) and DAPI to study their morphological features. MSCs have the potential to differentiate into various lineages ( Robert et al., 2020 ). Subsequently, the MSC were checked for their adipogenic and osteogenic differentiation characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…However, no study has ever been performed to evaluate MSM overall effects on progenitor cells and to understand how MSM may promote both osteogenic and chondrogenic differentiation. This is a particularly relevant aspect, since osteogenesis and chondrogenesis originate from the same progenitor cells and are highly regulated processes [39].…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro cell culture study also confirmed that BMSCs from osteoporotic rats had a stronger adipogenic differentiation ability than BMSCs from normal rats; in contrast, the osteogenic differentiation ability was weakened. In patients with all kinds of primary osteoporosis, the adipogenic differentiation of BMSCs in the bone marrow cavity increases with decreasing osteogenic ability, and the content of adipocytes is inversely proportional to the degree of osteoporosis, which further indicates that there is “one ebb and another” relationship between adipocytes and osteoblasts in the bone marrow, which has been considered the pathogenesis of primary osteoporosis ( Li et al, 2018 ; Muruganandan et al, 2020 ; Robert et al, 2020 ). Therefore, the new adipocytes formed by the directional differentiation of BMSCs have a close physiological and pathological correlation with fat and bone.…”
Section: Introductionmentioning
confidence: 99%